Uji Efektivitas Diuretik Infusa Daun Kelengkeng (Dimocarpus longan L.) Terhadap Tikus Putih (Rattus norvegicus) Jantan - Khairani . (Jurnal Penelitian Farmasi Indonesia, 2017)
Research has been done about the test of diuretic effectiveness on longan (Dimocarpus longan L.) leaves infusion to male white rat (Rattus norvegicus). The aim of this research is to see the diuretic effectiveness on (Dimocarpus longan L.) leaves infusion to male white rat (Rattus norvegicus). Based on the results that longan leaves infusion tested in male white rat with concentration of 20%, 40% and 80% showed increase urine volume in the test group of longan leaf infusion, but smaller than the urine volume in the positive control group.